Depression and Epilepsy: A New Perspective on Two Closely Related Disorders - Kanner, Andres M (Blackwell Science Inc, 2006)
Depression is the most frequent psychiatric comorbidity in epilepsy. Yet, it remains under-recognized and untreated in a significant number of patients. It may mimic primary depressive disorders, but in a significant percentage of patients, depression presents with atypical pleomorphic characteristics. The use of screening self-rating scales may help to identify depressive episodes in patients with epilepsy, but a diagnosis cannot be established by the sole use of these instruments without an additional, in-depth evaluation. Timely recognition and treatment of depression is of the essence in epilepsy patients, as its persistence is an independent predictor of poor quality of life, increased suicidal risk, greater use of health services, and higher medical costs not related to the psychiatric treatment. Neurologists will often find themselves in the position of being the only health care provider available to initiate treatment. Accordingly, they should be well trained to provide psychopharmacologic treatment for major depressive episodes, dysthymic disorders, and minor depression. However, patients with suicidal ideation, psychotic symptoms, or bipolar disorders should be referred immediately to the care of a psychiatrist.